Physical Exercise Induces Immunoregulation of TREG, M2, and pDCs in a Lung Allergic Inflammation Model - Fernandes, Paula; de Mendonça Oliveira, Luana; Brüggemann, Thayse Regina; Sato, Maria Notomi; Olivo, Clarice Rosa; Arantes-Costa, Fernanda Magalhães (Frontiers in Immunology, 2019)
The benefits of moderate aerobic physical exercise for allergic asthma are well known, particularly that of the anti-inflammatory effect that occurs by reducing Th2 responses and lung remodeling. However, the mechanisms of this immunoregulation are still under investigation. In this study, we investigated the possible immunoregulatory mechanisms of lung inflammation induced by moderate aerobic exercise in an experimental asthma model. BALB/c mice were distributed into Control, Exercise (EX), OVA, and OEX groups. OVA and OEX groups were sensitized with ovalbumin (OVA) on days 0, 14, 21, 28 and 42 and were challenged with OVA aerosol three times a week from day 21 to day 51. The EX and OEX groups underwent moderate aerobic physical exercise from day 21 to day 51 (5 d/w, 1 h/d). The mice were euthanized on day 52. We evaluated pulmonary cytokine production, serum immunoglobulin levels and the inflammatory cell profile in lung and mediastinal lymph nodes. OVA mice showed increased expression of IL-4, IL-6, IL-10, and TGF-β and decreased macrophage type 2 (M2) recruitment. Physical exercise did not affect the increased antibody production of IgG2a, IgG1, or IgE induced by OVA. Of note, physical exercise alone markedly increased production of anti-inflammatory cytokines such as IL-10 and TGF-β. Physical exercise in OVA-mice also increased the recruitment of M2 in the lungs, as well as the influx and activation of regulatory T cells (Tregs) and CD4 and CD8 lymphocytes. In the draining lymph nodes, it was also observed that physical exercise increased the activation of CD4 T cells, regardless of the presence of OVA. Notably, physical exercise decreased common dendritic cells’ (cDCs; pro-inflammatory) expression of costimulatory molecules such as CD80, CD86 and ICOSL in the draining lymph nodes, as well as increased ICOSL in plasmacytoid dendritic cells (pDCs; anti-inflammatory). Together, these findings show that physical exercise modulates pulmonary allergic inflammation by increasing Treg and M2 recruitment, as well as pDCs activation, which leads to an increase in anti-inflammatory cytokines and a decrease in pro-inflammatory cells and mediators.